NAMIDZAJ AL-MAWAD AL-TA'LIMIYAH LI BARNAMAJ AL-QARYAH AL-‘ARABIYAH LADA AL-THALABAH FIZ QISM TA'LIM AL-LUGHAH AL-‘ARABIYAH BI JAMI'AH JAKARTA AL-HUKIMIYAH - Setiadi, Syamsi; Susilowati, Indri (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
Qaryah Arabi>yah (QA) is an intensive Arabic language training activity for students of department of Arabic Language Education, Universitas Negeri Jakarta, for one full eight days with various Arabic-speaking activities. This program has been started since 2015 and then implemented as an annual activity. Until its implementation in the fourth year, there is no material module prepared to support the implementation of this QA. Thus, it is necessary to develop a material module that can be utilized by the QA committee. For this reason, this study uses a development research method, based on the adaptation of the ADDIE model with steps: Analysis, Design, Development, and Evaluation. Based on the results of the model design development, the results obtained by experts on the QA material module model in the excellent category. Thus, the only material model developed can be used properly and properly as a reference for teaching materials in activities of Qaryah Arabi>yah.